Outcomes of AI-Assisted Interventions to Reduce Nurse Burnout - Nawaz, Amna; Nisa, Qamar Un; Tahira, Yasmin; Taj, Shazia (Biological and Clinical Sciences Research Journal, 2025)
Burnout among nurses is a critical global concern that affects patient safety, job satisfaction, and healthcare quality. Artificial intelligence (AI)–assisted programs have emerged as innovative tools to support mental health and reduce occupational burnout through personalized monitoring and adaptive interventions. Objective: To evaluate the outcomes of artificial intelligence-assisted programs to mitigate burnout in nurses. Methodology: A case-control study was conducted in the Nursing Department of Nishtar Hospital, Multan, from March 2024 to March 2025. A total of 100 nurses working in the hospital for 1 year were included in the study. Nurses were divided into two groups: Group A (case group), comprising 50 nurses attending an AI-assisted burnout intervention program, and Group B (control group), comprising 50 nurses attending a self-selected burnout intervention program. The primary outcome was measurement of burnout on personal, work-related, and patient-related levels. Results: Patient-related burnout changed significantly between groups (F=7.68, p=0.001) and time (F=15.81, p<0.0001) over the duration of intervention. The same pattern was observed for personal burnout between groups (F=10.89, p<0.0001) and over time (F=17.7, p<0.0001). Nurses of both groups had significantly reduced job stress after either intervention (Group A: t=2.99, p=0.005; Group B: t=2.68, p=0.010). The stress response was also reduced considerably between both groups after programs (Group A: t= 1.99, p=0.040; Group B: t=2.82, p=0.008).Conclusion: AI-assisted interventions significantly reduce nurses' burnout, especially at the personal and patient levels.